PENGAKTIFKAN KEMBALI PEMBERHENTIAN TIDAK DENGAN HORMAT APARATUL SIPIL NEGARA (STUDI PUTUSAN NO.26/G/2019/PTUN. GTO): Reactivation Of Dismissal Without Honor Of State Civil Apparatus (Study Of Decision No. 26/G/2019/Ptun.Gto) - Innayah Sismitha Abd Wahab; Andari Yurikosari (Reformasi Hukum Trisakti, 2025)
Bone Bolango Regency, as part of Indonesia's administrative entity, oversees a number of State Civil Apparatus (ASN) who perform vital functions in maintaining government stability and providing the best services to the public. However, in practice, there are cases showing dismissals of ASNs that do not align with the legal principles and ethical norms in force. The dismissal of State Civil Apparatus (ASN) without honor not only affects the individual concerned, but also reflects the quality of the public administration system in Bone Bolango Regency. The problem statement in this article is: How to reactivate ASNs dismissed without honor, and what are the legal consequences of the dismissal decision issued by the Regent of Bone Bolango? The research method used is normative juridical research. The result and the conclusion of this article is that reactivation is possible after the issuance of the decision letter by the Regent of Bone Bolango, on the grounds that it was made without referring to and considering the applicable laws. The legal consequence of the Dismissal Decision without honor for ASN in Bone Bolango Regency is that the individual concerned is not allowed to return to active civil servant status anywhere